The collapse of megafaunal populations in southeastern Brazil. Issue 1 (17th August 2017) - Raczka, Marco F.; Bush, Mark B.; De Oliveira, Paulo Eduardo
Abstract: Whether humans or climate change caused the extinction of megafaunal populations is actively debated. Caves in the Lagoa Santa provide mixed assemblages of megafauna and human remains; however, it remains uncertain the extent to which humans and megafauna interacted or overlapped temporally. Here we present the first paleoecological record from lowland South America that tracks the decline of megafauna and its ecological implications. We provide a data set for pollen, charcoal, and Sporormiella, from two lakes in southeastern Brazil that span the last 23, 000 yr. The data showed reduced abundances of Sporormiella and an inferred megafaunal population decline that began 18, 000 yr ago, with the functional extinction occurring between 12, 000 and 11, 500 yr ago. Population declines coincided with wet events. The age of the final megafaunal decline is within the range of the first human occupation of the region. Our data are consistent with climate causing the population collapse, with humans preventing population recovery and inducing extinction. We did not observe some of the ecological repercussions documented at other sites and attributed to the megafaunal extinction. Habitat-specific ecological consequences of the extinction add to the heterogeneity of late Pleistocene and early Holocene landscapes.